Socio-economic implications for teachers retrenched in Qwaqwa, 1996 - 1999 - Phakisi, Lehlomela Stanley (University of the Free State (Qwaqwa Campus), 2005)
The purpose of this research was to investigate the socio - economic effects of teacher retrenchments in Qwaqwa - Free State. The administration of the survey method generated information that was analysed using both qualitative and quantitative techniques. The findings indicate that retrenchments severely affected the income and social status of teachers in the study area.
Dissertation (M.A. (Development Studies & Conflict Resolution))--University of the Free State (Qwaqwa Campus), 2005
Keywords: Teachers -- Dismissal of -- South Africa -- Qwaqwa; Teachers -- South Africa -- Qwaqwa -- Economic conditions; Teachers -- South Africa -- Qwaqwa -- Social conditions